BEACONDRIOD: AN AUTOMATED STUDENT ATTENDANCE SYSTEM - ALI, AREE; NADIR, BAMO (Journal of Duhok University, 2021)
Until today, student attendance taking proves to have remained as one of the most challenging tasks in educational organizations. Time efficiency, authenticity together with cost have been major influential factors for many proposed systems in the past to tackle such a challenging task. Nevertheless, such proposed systems lack one or more of these issues. This paper introduces an idea in which smartphones owned by students and teachers are used as the main building blocks of an attendance system that addresses these three major issues. The proposed system takes advantage of the built-in Bluetooth Low Energy (known as BLE) of the smartphones such that it turns them into Beacon Transmitters and Receivers. Two different applications are developed, one of which is installed on the student smartphones turning into a Beacon Transmitter while the other is installed on the instructor’s device acting as a Beacon scanner. Students are automatically marked as present, once s/he enters the classroom with the app running. When the instructor is satisfied with the attendance, s/he can send the data to a remote server.